PENGARUH INOVASI DAN ENTREPRENEURIAL ORIENTATION TERHADAP KEUNGGULAN BERSAING UMKM DI KOTA MAKASSAR - Nurul Fadilah Aswar; M. Ikhwan Maulana Haeruddin; Ilma Wulansari Hasdiansa (Jurnal Bisnis dan Kewirausahaan, 2023)
Abstract should end with a comment about the importance of the results or conclusions brief. The existence of micro, small and medium enterprises (MSMEs) plays an important role in economic growth. One of their most important tasks in economic growth is to revive economic dynamics. Even though MSMEs have been proven to have a strategic role in the Indonesian economy, it does not mean that MSMEs do not face various challenges and limitations in doing business. Innovation and Entrepreneurial orientation are necessary for businesses to remain relevant to consumers, and several studies have also shown that innovation can help MSMEs grow and be able to identify new opportunities and make new combinations of their resources. This research is a conclusive research design that uses a single cross-sectional as a data collection method by means of a survey. The sampling method is a non-probability method and purposive sampling technique. The estimation method used in this research is Maximum Likelihood. This study uses the method of regression analysis to measure the influence of the independent variables on the dependent variable. The results of this study indicate that (1) Innovation has a positive and significant effect on competitive advantage for MSMEs in Makassar City. (2) Entrepreneurial orientation has a positive and significant effect on the competitive advantage of MSMEs in Makassar City.